The Origin of Christian Doctrine of Sacrifice - ., JOD (Journal of Dharma, 1980)
Robert J. Daly S.J.,The Origin of Christian Doctrine of Sacrifice, London, Darton, Longman. Todd Ltd., 1978, pp. vii +152, £ 2·50.